Projeto de uma bancada didática de uma bomba centrífuga de três estágios modular - SANTOS, Rickson Igor Bibas dos (2023)
The purpose of this work is to develop the design of a modular multistage pump with three identical stages, which can operate with one, two or three independent stages, using the knowledge obtained in the literature, with the aim of making it possible to use, in the future, -rarely, this pump as a didactic bench in disciplines and research in the field of fluid mechanics. In this work a bibliographic review is presented, followed by a theoretical foundation on the operation of a centrifugal pump, types of hydraulic machines and their peculiarities, in sequence, the development of the project is treated and the reasons that culminated in the choice of the presented methodology. At the end of the work, the details of the pump components and their presentation in different configurations proposed by the author are exposed. Improvements can be incorporated into the project, such as the development of a range of rotors with different characteristics to be tested, as well as the operation with more stages in order to verify how the energy gain occurs with the increase in the number of stages.